2018
DOI: 10.1111/pbi.12906
|View full text |Cite
|
Sign up to set email alerts
|

An oligosaccharyltransferase from Leishmania major increases the N‐glycan occupancy on recombinant glycoproteins produced in Nicotiana benthamiana

Abstract: SummaryN‐glycosylation is critical for recombinant glycoprotein production as it influences the heterogeneity of products and affects their biological function. In most eukaryotes, the oligosaccharyltransferase is the central‐protein complex facilitating the N‐glycosylation of proteins in the lumen of the endoplasmic reticulum (ER). Not all potential N‐glycosylation sites are recognized in vivo and the site occupancy can vary in different expression systems, resulting in underglycosylation of recombinant glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 76 publications
4
72
0
Order By: Relevance
“…Previous studies in mammals have indicated an important role of the tailpiece N-glycan for JC incorporation (Atkin et al, 1996;Sørensen et al, 2000). In plant-produced IgAs, the tailpiece is incompletely glycosylated which might contribute to inefficient dimeric IgA formation (Westerhof et al, 2015;Göritzer et al, 2017;Castilho et al, 2018). Underglycosylation was even more pronounced in the IgA2m(2) isotype which also exhibited higher amounts of non-assembled monomeric IgA when co-infiltrated with the JC.…”
Section: Increased N-glycosylation Of the Tailpiece Promotes Dimeric mentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies in mammals have indicated an important role of the tailpiece N-glycan for JC incorporation (Atkin et al, 1996;Sørensen et al, 2000). In plant-produced IgAs, the tailpiece is incompletely glycosylated which might contribute to inefficient dimeric IgA formation (Westerhof et al, 2015;Göritzer et al, 2017;Castilho et al, 2018). Underglycosylation was even more pronounced in the IgA2m(2) isotype which also exhibited higher amounts of non-assembled monomeric IgA when co-infiltrated with the JC.…”
Section: Increased N-glycosylation Of the Tailpiece Promotes Dimeric mentioning
confidence: 97%
“…For endoplasmic reticulum resident protein 44 (ERp44) expression, a codon-optimized coding sequence of human ERp44 (CAC87611) including the sequence coding for the signal peptide from barley alpha-amylase was synthesized by GeneArt and cloned into the XbaI/BamHI sites of pPT2M. The expression construct of the single-subunit oligosaccharyltransferase from Leishmania major (LmSTT3D) has been described previously (Castilho et al, 2018).…”
Section: Construct Design and Cloningmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the case of HIV-1 Env, many of the broadly neutralizing antibodies isolated from natural infection target epitopes that contain a glycan component suggesting that a recombinant immunogen should reproduce these structures (Crispin et al, 2018). Encouragingly, a recent publication by Castilho and colleagues has suggested the coexpression of a Leishmania major oligosaccaryltransferase can be used to improve the glycan occupancy of plant-derived proteins (Castilho et al, 2018). Furthermore, ongoing efforts to humanize the glycosylation of recombinant plant-produced proteins have demonstrated the successful removal of plant-specific N-glycan moieties and the introduction of human glycosyltransferases in planta (Strasser et al, 2014).…”
Section: The Potential Impact Of Plant-derived N-glycosylationmentioning
confidence: 99%
“…Plant expression vectors were assembled using standard recombinant DNA technology, as previously described [51]. The KPF1-Antx and isotype control antibody expression vectors, which included heavy chain (HC) and light chain (LC) genes, were co-expressed with an oligosaccharyltransferase from Leishmania major (LmSTT3D) known to enhance N-glycan occupancy of recombinant proteins, using a similar strategy to that previously described [52]. In addition, a third expression vector was utilized to enhance recombinant protein expression by transiently silencing Argonaute1 (AGO1) and Argonaute4 (AGO4) proteins to minimize post-transcriptional gene silencing (PTGS) [Patent WO 2019/023806 A1].…”
Section: Methodsmentioning
confidence: 99%